Iron metabolism inorganic biochemistry and regulatory mechanisms - Franco, Ricardo; Moura, José J. G.; Ferreira, Glória C. (Wiley-VCH, 1999)
Iron plays a crucial role in many biochemical processes. In recent years intensive research has led to a better understanding of the function of iron in cellular metabolism. In more than twenty articles internationally renowned experts give a thorough account of the recent developments of this fascinating field. The book focuses on the central questions, e.g. transport, storage, and utilization of iron in cells, the three-dimensional structure of iron-containing proteins, the physiological function of heme and iron sulfur-containing proteins, and the regulatory mechanisms in heme biosynthesis and redox regulation of signal transduction.